Percent plans, automatic admissions, and college outcomes - Lindsay Daugherty; Paco Martorell; Isaac McFarlin (IZA Journal of Labor Economics, 2014)
Access to selective universities is highly coveted because of the perception that attending one provides opportunities otherwise difficult to obtain. To broaden access to the state's flagship universities in a manner that does not rely on conventional affirmative action, Texas passed the Top Ten Percent Plan in 1997, which guarantees automatic admission to any public university in the state to students in the top decile of their high school class. We estimate the effect of eligibility for automatic admissions on college choice and persistence for students in a diverse urban school district. Regression discontinuity estimates show that eligibility for guaranteed admissions has a substantial impact on enrollments at Texas flagship universities and increases the number of semesters enrolled at flagships. The increase in flagship enrollments appears to displace enrollments in private universities but has no effect on overall college enrollment or the quality of college attended. The effects are concentrated in schools that have high college-sending rates (relative to other schools in the district), suggesting that automatic admissions may have little effect on students in the most disadvantaged schools.
Keywords: I2; 330